Indigenous element on school instructional leaderships model in Malaysia: A literature review: Elemen-Elemen Watan Dalam Model Kepimpinan Instruksional Sekolah Di Malaysia: Satu Tinjauan Literatur - Samichan, Aziah binti; Yunus, Jamal @ Nordin bin; Awang, Marinah binti (Jurnal Pendidikan Bitara UPSI, 2021)
Instructional leadership is the most basic style of leadership that school leaders need to master. This is because instructional leadership is deemed to have a significant relationship to student learning, teacher teaching competence, and hence school performance. Instructional leadership styles are still seen to be relevant based on the emergence of various instructional leadership models over the past four decades. The evolution of the instructional leadership model pioneered by western scholars has crossed continental borders to include Malaysia. However, do the Western instructional leadership models that form the reference for most educational leaders in Malaysia meet the educational context of our country? It is common knowledge that western instructional leadership models are environmentally and culturally oriented to the West and European nations. Therefore, the purpose of this concept paper, in article format, is to explore the need to develop a Malaysian model of instructional leadership, based on literature reviews. By reviewing the literature from 2000 to 2020, the researcher will analyze the instructional leadership models developed by local scholars, focusing on the proposed elements. The results of this study are expected to help the researcher formulate the main elements of the proposed instructional leadership model. Subsequently, these findings are expected to help researchers form judgments concerning the selected issues covered in this study.